Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2147/imcrj.s108855
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic retinopathy associated with Crohn’s disease

Abstract: PurposeTo report a case of a patient with ischemic retinopathy associated with Crohn’s disease.Case reportThis report presents a case of a 28-year-old female patient with Crohn’s disease and sudden decrease of visual acuity in the right eye. Fluorescein angiography, optical coherence tomography, and multifocal electroretinography confirmed the clinical features of ischemic retinopathy. After systemic corticosteroid treatment, the patient developed epiretinal membrane without significant improvement in visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Extra intestinal manifestations of CD are commonly prevalent including cholelithiasis, anemia, inflammatory arthropathies, erythema nodosum, osteoporosis, nephrolithiasis, venous thromboembolism, scleritis, and uveitis [20]. Ocular manifestation is one of the important extra-intestinal manifestation of CD with a reported incidence of 4% to 10% including episcleritis, scleritis, conjunctivitis, anterior uveitis, orbital pseudotumor, optic neuritis, marginal keratitis, retinal vascular occlusive disease, and retinitis, as reported by Mady [23], however Siqueira's reported up to 12% with the majority of iritis, uveitis, episcleritis, and conjunctivitis [24].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Extra intestinal manifestations of CD are commonly prevalent including cholelithiasis, anemia, inflammatory arthropathies, erythema nodosum, osteoporosis, nephrolithiasis, venous thromboembolism, scleritis, and uveitis [20]. Ocular manifestation is one of the important extra-intestinal manifestation of CD with a reported incidence of 4% to 10% including episcleritis, scleritis, conjunctivitis, anterior uveitis, orbital pseudotumor, optic neuritis, marginal keratitis, retinal vascular occlusive disease, and retinitis, as reported by Mady [23], however Siqueira's reported up to 12% with the majority of iritis, uveitis, episcleritis, and conjunctivitis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Barabino found that the most common complications are episcleritis, scleritis, and uveitis occurring in up to 29%, 18% and 17% of patients, respectively [25], while Katsanos found that Posterior scleritis and orbital inflammatory disease (orbital pseudotumor) are the most commonly existing [24], and Mady found that the commonest among them is episcleritis [23]. On the other hand, the incidence of the involvement of the posterior segment is less than 1% as it is very rare [24], while the reported incidence by Barabino, ranges between less than 1% to 30% [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations